(untitled) (Research, Society and Development, 2024)
Introduction: There are millions of microorganisms living in the human intestine, and this system is called the gastrointestinal microbiota. Its functions are: digestion and absorption of nutrients; immune regulation; protection against pathogens; integrity of the intestinal barrier. Objective: Understand how the intestinal microbial community can impact mental state, especially depressive and anxiety disorders. Also understand the connection between the microbiota and its influence on the brain and nervous system, called the gut-brain axis, and the relevance of the bidirectional and complex network that exists between the intestinal microbiota and the Central Nervous System (CNS), which has a important relationship in the regulation of behavior (stress), as well as in the pathophysiology of psychological disorders of anxiety and depression. Methodology: A literature review will be carried out, selecting articles from the years 2015 to 2024 in Portuguese and English. The databases searched will be PubMed, Google Scholar, CAPES, SciELO and EBSCOhost. Expected results: Studies highlight that modulating the microbiota through probiotic supplementation can not only restore microbial diversity, but also significantly reduce depressive symptoms and improve patients’ quality of life. Probiotics have the ability to influence the interaction between the intestine and brain through the production of neurotransmitters.